Livestock identification and traceability systems in the Intergovernmental Authority on Development (IGAD) region: Proceedings of a regional workshop, Addis Ababa, Ethiopia, 4-5 February 2014 - International Livestock Research Institute (International Livestock Research Institute, 2014)
Livestock identification and traceability systems (LITS) enhance livestock production and trade by enabling improved surveillance and management of infectious diseases, control of livestock movement and effective delineation of production systems through zoning and compartmentalization and improved access to information along market chains. LITS have also been used to deter stock theft in areas that are prone to cattle rustling (cattle theft). In a meeting held in Argentina in March 2009, the World Organization for Animal Health (OIE) and its members resolved to progressively implement LITS as per the Terrestrial Animal Health Code for fairer and broader international trade of animals and animal products.